2002
DOI: 10.1007/s00464-001-9190-7
|View full text |Cite
|
Sign up to set email alerts
|

Specific hygiene issues relating to reprocessing and reuse of single-use devices for laparoscopic surgery

Abstract: None of the reprocessed SUDs were effectively cleaned or sterilized. This may provide an opportunity for survival and growth of non-resistant or nosocomial organisms and viruses. The use of such inadequately reprocessed SUDs increases the risk for the patient, and can lead to nosocomial infection and to legal consequences for the health care facility.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0
3

Year Published

2004
2004
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 3 publications
(4 reference statements)
0
24
0
3
Order By: Relevance
“…In reviewing the literature only one study (3) was found that aimed to evaluate the achievement of sterilization of laparoscopic scissors -one of the devices studied in this investigation. In that study, the sterilization of laparoscopic scissors was not achieved.…”
Section: Introductionmentioning
confidence: 99%
“…In reviewing the literature only one study (3) was found that aimed to evaluate the achievement of sterilization of laparoscopic scissors -one of the devices studied in this investigation. In that study, the sterilization of laparoscopic scissors was not achieved.…”
Section: Introductionmentioning
confidence: 99%
“…It may also arise due to inadequate decontamination of the laparoscope or other laparoscopic instruments. Some studies have suggested that disposable devices can not be successfully decontaminated even Costs estimated in US $ Data expressed as means ± SD when current practices are followed carefully and that they may suffer material destruction during the procedure [19]. Residual bioburden on insufficiently cleaned devices may hamper disinfection as well as sterilization procedures and may account for nosocomial infection [3].…”
Section: Discussionmentioning
confidence: 99%
“…Residual bioburden on insufficiently cleaned devices may hamper disinfection as well as sterilization procedures and may account for nosocomial infection [3]. Roth et al found that some bioburden remained on the reused disposable instruments; however, all disposable devices contaminated with Pseudomonas aeruginosa or Staphylococcus aureus were effectively disinfected [19]. Moreover, the cell walls of either viable or inactivated bacteria in residual material may release lipopolysacchrides with pyrogenic activity, thus creating another potential hazard [18].…”
Section: Discussionmentioning
confidence: 99%
“…These conflicting results were apparent for anaesthesia devices (Daggan et al, 1999;Lipp et al, 2000), airways devices (Vezina et al, 2001), and disposable plastic trocars (Chan et al, 2000;Roth et al, 2002). The reprocessing and reuse of sphincterotome devices was considered safe and effective with proper reprocessing standards (Kozarek at al., 1999).…”
Section: The Current Status About Reprocessing Sudsmentioning
confidence: 99%